Sosialisasi Zero Waste dan coaching clinic pengolahan sampah di Desa Labuhan Haji - Agus Muliadi Putra; Husnayati Hartini; Baiq Liana Widiyanti; Haerudin Haerudin (Universitas Hamzanwadi, 2021)
Every human activity will always produce residues called garbage and waste. Garbage is usually identical to the rest of daily processing in solid form, while waste is the rest of the processing in liquid. Both waste and garbage will continue to increase in line with increasing human activities and population growth. Changing the public's perspective on waste from being considered a waste material that has no benefits to being helpful is an integral part of Zero Waste education and socialization efforts. The purpose of this activity is to socialize the people of Labuhan Haji Village about Zero Waste. This socialization consists of three activities, namely: 1) education about Zero Waste materials; 2) demonstration or practice of processing waste cooking oil into candles and soap; 3) coaching clinic on waste management (collection, sorting, weighing, and analysis of waste composition). The method used is lecture, demonstration, practice, and discussion. Location of activities in Labuhan Haji Village and Lab. Environmental Engineering Study Program, Faculty of Engineering, Hamzanwadi University. The implementation of the activity showed an increase in knowledge and awareness of the importance of the Zero Waste program in the people of Labuhan Haji Village. In addition, the community can process used cooking oil into more valuable goods and process waste properly.